Systematic review into factors associated with the recruitment crisis in psychiatry in the UK: students', trainees' and consultants' views. (December 2017) - Choudry, Abid; Farooq, Saeed
Abstract : Aims and method: To review the literature to examine the factors that may be affecting recruitment into psychiatry in the UK. We systematically searched four databases to identify studies from 1974 to 2016 and identified 27 papers that met the specified inclusion criteria. Results: Most papers ( n = 24) were based on questionnaire surveys. The population in all studies comprised of 1879 psychiatrists, 6733 students and 220746 trainees. About 4–7% of students opt for a career in psychiatry. Enrichment activities helped to attract students more towards psychiatry than just total time spent in the specialty. Job content in terms of the lack of scientific basis, poor prognosis and stigma towards psychiatry, work-related stress and problems with training jobs were common barriers highlighted among students and trainees, affecting recruitment. Job satisfaction and family-friendly status of psychiatry was rated highly by students, with lifestyle factors appearing to be important for trainees who tend to choose psychiatry. Clinical implications: Negative attitudes and stigma towards psychiatry continue to persist. Teaching and training in psychiatry needs rethinking to improve student experience and recruitment into the specialty.